Capsaicin inhibits the metastasis of human papillary thyroid carcinoma BCPAP cells through the modulation of the TRPV1 channel. Issue 1 (29th November 2017) - Xu, Shichen; Zhang, Li; Cheng, Xian; Yu, Huixin; Bao, Jiandong; Lu, Rongrong
Abstract : Capsaicin inhibits metastasis of human papillary thyroid carcinoma BCPAP cells through modulation of the TRPV1 channel. Abstract : Capsaicin (CAP), a potent transient receptor potential vanilloid type 1 (TRPV1) agonist, is a major ingredient of red pepper. Recently, capsaicin has attracted increasing attention owing to its multiple biological activities. However, the anticancer effects of capsaicin against various types of cancers, especially on thyroid carcinoma, have not been completely elucidated. TRPV1, which can be activated by capsaicin, plays a key role in many biological and physiological processes. In the present study, the anticancer properties of capsaicin against papillary thyroid cancer BCPAP cells were investigated. Our results indicated that TRPV1 and TRPV6 were universally expressed in different types of thyroid cell lines. Capsaicin could inhibit multiple steps of metastasis without affecting the viability of BCPAP cells. The activation of TRPV1 by capsaicin (25–100 μM) significantly suppressed the migration and invasion of BCPAP cells as well as their adhesion. The protein levels of Snail1 and Twist1, two critical EMT transcription factors (EMT-TFs), dramatically decreased in a dose-dependent manner after capsaicin treatment, accompanied by the up-regulation of downstream protein E-cadherin. Subsequently, the activation of TRPV1 by capsaicin also caused significant inhibition of the expression of MMP-2 and MMP-9. Moreover, the inhibitory effects of capsaicin on the metastasis of BCPAP cells were abrogated by the pre-treatment of a specific TRPV1 antagonist (capsazepin). Our results suggest that the activation of TRPV1 by capsaicin is associated with the metastatic inhibition of papillary thyroid cancer BCPAP cells, indicating that targeting of TRPV1 functions remains a feasible strategy for cancer treatment.